One Health Requires a Theory of Agency - Capps, Benjamin (Cambridge quarterly of healthcare ethics, 2022)
One health suggests that human and animal health are comparable, but in practice, the concept aligns with the principles of public health ethics. One health ethics, as such, appears to eschew connotations of equality for the natural world. A theory of agency revises that anthropocentric assumption. This article begins with a critique of environmental dualism: the idea that human culture and nature are separate social realms, thus justifying public health as a (unifying) purpose. In response, this article argues that, first, a neuroethics of one health might equally regard humans and (some) animals, which have comparable mental states, as rational agents. Second, rational agency should ground our moral connections to nature in terms of the egalitarian interests we have (as coinhabitants) in the health of the planet. While this article makes a moderate case for interspecific rights (as the first argument asserts), neuroscience is unlikely for now to change how most public institutions regard nonhuman animals in practice. However, the second argument asserts that rational agency is also grounds for philosophical environmentalism. One health ethics, therefore, is a theory of equality and connects culture to nature, and, as such, is a separate, but coextensive approach to that of public health.